Unraveling metabolic shifts in peach under agrochemical treatments during flower bud endodormancy in the context of global warming - Guillamón, Jesús Guillamón; Yuste, José Enrique; López-Alcolea, Jesús; Dicenta, Federico; Sánchez-Pérez, Raquel (Frontiers in Plant Science, 2025)
IntroductionIn Mediterranean areas like Spain, global warming has endangered stone fruit production by reducing chill accumulation, leading to significant agronomical and economical losses. To mitigate this issue, agrochemicals have been applied for decades to promote endodormancy release and initiate flowering. However, many of these chemicals have been associated with strong phytotoxicity, resulting in their recent ban. As a result, identifying novel pathways to modulate endodormancy release is critical and essential for developing effective, non-toxic agrobiochemicals.MethodsIn this study, we investigated the effect of two different agrochemicals mixes: 1% Broston® + 5% NitroActive® and 3% Erger® + 5% Activ Erger®, sprayed on peach trees during endodormancy over two years, followed by non-target metabolomic analyses on flower buds to identify metabolic changes in treated versus control trees.Results and discussionSignificant variations were observed in metabolites from the abscisic acid and phenylpropanoid pathways. Notably, six types of phospholipids were identified, with most increasing exclusively in treated samples during endodormancy release. These results were in concomitance with the increased expression of 4-coumarate-CoA ligase 1, 9-cis-epoxycarotenoid dioxygenase, and xanthoxin dehydrogenase genes. In a subsequent validation experiment performed in the third year, branches treated with phospholipids and cinnamic, caffeic, and abscisic acids advanced endodormancy release by one to two weeks, which represents the first evidence of endodormancy release modulation by the use of these metabolites. Moreover, this study contributes to our understanding of the biochemical mechanisms involved in endodormancy release and highlights the potential of phenylpropanoids, phospholipids, and related compounds as targets for developing sustainable agrochemicals, addressing challenges posed by climate change to Prunus spp. cultivation.